The Effect of Spark Current Tuning on the Formation of Cu Nanoparticles Synthesized by Spark Ablation in Nitrogen Atmosphere - Maria Assunta Signore; Antonio Della Torre; Antonio Serra; Daniela Manno; Rosaria Rinaldi; Marco Mazzeo; Luca Nunzio Francioso; Luciano Velardi (Crystals)
The demand for a “green” approach to the synthesis of nanomaterials is becoming increasingly pressing. In response to this need, we present, for the first time, the use of spark ablation as an environmentally friendly deposition technique to obtain nanoparticles of copper nitride, a material that is gaining increasing attention in the field of photovoltaic advanced technologies. This method involves the ablation of pure copper electrodes in nitrogen atmosphere while a spark current is tuned. The overall result is the co-presence of nitride and oxide nanoparticle agglomerates with different sizes according to the spark current, as confirmed by X-ray diffraction, Raman spectroscopy, X-ray photoelectron spectroscopy and energy-dispersive spectroscopy techniques. Scanning probe microscopy and scanning electron microscopy show an increase in the number and size of nanoparticle agglomerates with an increasing current, while the nanoparticle size is always about sub-10 nm. The findings of this work promote spark ablation as a simple, versatile, cost-effective, environmentally friendly deposition method to obtain nitride-based nanoparticles. Furthermore, it is compatible with many types of materials and substrates, increasing the possible combinations of metals/semiconductors and carrier gas types to obtain completely innovative materials with unique compositions and properties.